Transformasi Nilai-Nilai Sila Keempat Pancasila dalam Kehidupan Demokrasi Indonesia - Maria Kristina Nau; Tekla Dua Ona; Hendrika Doa; Grasiana Sandara Mugi; Flaviana Loda; Hildegardis Jesika Beka (International Forum of Researchers and Lecturers, 2025)
The fourth principle of Pancasila, “Democracy guided by the inner wisdom of deliberation/ representation,” serves as the foundation of Indonesia’s democratic system. The values of democraty, deliberation, wisdom, and representation reflect the unique characteristics of Pancasila democracy, distinguishing it from other democratic systems. This article aims to analyze the transformation of these vaules in Indonesia’s democratic life, both in governance and society. This research uses a qualitative method with a descriptive-analytical approach through literature reviews, legal regulations, and observations of Indonesia’s democratic pratices. The findings reveal that the implementation of the fourth mechanisms such as elections and representative institutions. However, challelnges such as corruption, money politics, low public participation, and a lack of Pancasila education remain significant obstacles. The transformation of the fourth principle requires strengthening Pancasila education, leadership integrity, and active public participation. With these efforts, Pancasila democracy can evolve into a system that upholds justice, deliberation, and prioritizes the people’s interests.